Development of hots-based cognitive assessment instruments: ADDIE model - Maxnun, Lu'luil; Kristiani, Kristiani; Sulistyaningrum, Cicilia Dyah (Journal of Education and Learning (EduLearn), 2024)
Higher order thinking skills (HOTS) are an important element in facing the challenges of the 21 st-century. Difficulty in solving problems systematically, facing challenges in an organized manner, and being unable to design original solutions are due to the low HOTS that students have. HOTS ability can improve students who low-level thinking skills in several ways, for example, through learning integrated with media, practice, and assessment or HOTS-based cognitive assessment. The purpose of this study was to develop and implement a HOTS-based cognitive assessment to assess students' HOTS abilities. The device development model used is an adaptation of the analysis, design, development, implementation, and evaluation (ADDIE) model. The research sample consisted of 30 students in class 11 of the Governance and Office Automation Competency Program of Vocational High School 1 Kudus. The result is that 11 students have the HOTS ability with very good criteria, 17 well criteria, and 2 enough criteria. This study suggests that a test instrument for further research is to measure students' HOTS ability. The Experts conclude that HOTS-based cognitive assessment can be used as an approach to improve students' HOTS to actively think selectively and supported by logical argumentation.